2015
DOI: 10.1016/j.jsurg.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Risks of Basic Urological Procedures Performed by Junior and Senior Residents

Abstract: Present performance of basic urological procedures involves a high percentage of unintended events, especially in TRUSP and TURBT, which are mainly caused by human factors and are a potential threat for patient safety. Junior residents are less independent but more thorough in the performance of UCS and TRUSP than senior residents are. Targeted skills training including assessment should be implemented before privileges for independent practice are granted to reduce the incidence of unintended events and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In 19 studies, events with deviations were analyzed, including incidents, 16 , 24 , 26 , 30 32 , 34 , 36 UEs, 22 , 27 , 28 , 33 , 35 errors, 12 , 21 , 25 and adverse events. 23 , 29 , 37 In almost all (n = 7) of the studies analyzing incidents, a clear definition of “an incident” was mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 19 studies, events with deviations were analyzed, including incidents, 16 , 24 , 26 , 30 32 , 34 , 36 UEs, 22 , 27 , 28 , 33 , 35 errors, 12 , 21 , 25 and adverse events. 23 , 29 , 37 In almost all (n = 7) of the studies analyzing incidents, a clear definition of “an incident” was mentioned.…”
Section: Resultsmentioning
confidence: 99%
“… 23 , 29 , 37 In almost all (n = 7) of the studies analyzing incidents, a clear definition of “an incident” was mentioned. For example: “A critical incident was defined as an event that had actual or potential harmful effects on the outcome of the management of a patient or group.” 33 Unintended events were defined as “a broader group of events—including near misses—that do not necessarily result in patient harm.” 22 , 27 , 28 , 32 , 35 The adverse events in the study by Zegers et al 37 and Merten et al 23 were defined as “unintended injuries among patients that results in disability, death or prolonged hospital stay, and is caused by health care management.”…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One could question the need for basic urological skills training for experienced, final-year residents or highly technically skilled residents. Interestingly, a recent study showed that a high percentage of unintended events occurred in basic urological procedures performed by junior as well as senior residents [26]. This indicates that 'being a senior resident' does not automatically exclude the need for basic urological skills training, and suggests the need for objective assessment of skills in the integration of a more personalized approach.…”
Section: Vriesmentioning
confidence: 99%
“…Thirdly, we analyze the data with exploratory factor analysis to identify the relationships between the maternal health risk factors and we further discuss our findings to establish the factors that healthcare experts and managers can prevent as avoidable and those that they can only mitigate as unavoidable. Finally, we discuss the study's contribution to the literature on maternal health care (Mackintosh & Sandall, 2016;Callister & Edward, 2016;Izugbara & Wekesah, 2018;Okonofua et al, 2017) and PRISMA operationalization (Fluitman et al, 2016;De Vries et al, 2015;van Galen et al, 2016;Martijn et al, 2012) and introduce a new dimension to maternal healthcare management through our PRISMA based questionnaire (PRMQ) that provides a holistic clinical data collection instrument for managing patient safety.…”
Section: Introductionmentioning
confidence: 99%